Identifying the problems, solutions, and challenges in referral writing: A Scoping Review - Faryal Azhar , Tausief Fatima , Rehan Ahmed Khan , Raheela Yasmin , Usman Mehboob (Journal of Rawalpindi Medical College, 2021)
Abstract Background Both primary care physicians and other specialists are not satisfied with the quality and content of written communication between colleagues(1). There is need of identifying the factors that lead to this dissatisfaction. Many of these are discussed in literature such as communication skills, teaching and assessment of referral writings to undergraduates, and lack of validated tool for evaluation of referral(2). This article is scoping review of literature for finding the problems, solutions, and challenges in referral writing. Methods The databases utilized for finding various referral systems are PubMed, ERIC, Pakmedinet and Google scholar. The article included in the study was 12 which were identified through PRISMA. These 12 articles were reviewed by two authors. (FA and TA) The first step was the application of Qualsyst criteria and then the two authors analyzed the final 12 articles for thematic analysis independently. Results The problems, solutions and challenges in referral writing were found after the thematic analysis by two authors. The multiple challenges regarding referral writing include the fact that details about the inadequate data written in referral letters, lack of teaching and learning strategies and lack of proper communication between physicians. There are many solutions like teaching and assessing the referral writing skills, introducing reflection and feedback to improve the skill among young doctors. Moreover, teaching the art of referral writing should include in the medical curriculum. Conclusion Referral writing is an important part of medical communication. A good quality referral will save time in management of patients. It will also enhance the outcome of patient management. There is need of teachings about communication skills in undergraduates and postgraduates students.